Multi-omics characterization of aflatoxigenic Aspergillus from grains and rhizosphere of maize across agroecological zones of Cameroon - Rolly Audrey Mvogo Nyebe; Aundy Kumar; Eddy Léonard Ngonkeu Mangaptche; Shanu Kumar; Shanmugam Velmurugan; Charishma Krishnappa; Aditi Kundu; Viviane Djuikwo; Deeksha Joshi; Robin Gogoi; Elie Fokou (Scientific Reports)
Abstract Maize (Zea mays L.) is the most widely consumed cereal in Cameroon but is frequently contaminated with aflatoxins, posing significant economic, environmental, and health risks. These challenges hinder progress toward the UN Sustainable Development Goals (SDGs) and Cameroon’s 2020–2030 National Development Strategy. A sustainable approach to managing aflatoxin contamination is biocontrol, which relies on naturally occurring atoxigenic fungi to suppress toxigenic strains. Although biocontrol strategies have been widely explored globally, their application in maize production and storage in Cameroon remains limited. This study aimed to establish a foundation for aflatoxin biocontrol by characterizing Aspergillus flavus strains associated with maize in Cameroon using a multi-omics approach. Characterization was performed using culturomic, microscopic, genomic, metabolomic, and targeted gene expression analysis techniques. Thirteen A. flavus L-morphotype strains were identified, including seven endophytic strains from maize seeds and six from the rhizosphere. All strains were confirmed as aflatoxigenic through ammonia vapor and UV tests, as well as metabolomic analysis, which identified cyclopiazonic acid, gliotoxin, and kotanin as core secondary metabolites, and quantified different aflatoxins in all the 13 strains. Gene analysis revealed seven distinct aflatoxin biosynthesis genotypes, with the aflC gene playing a key role in aflatoxin production. qRT-PCR results showed lower expression of aflatoxin biosynthesis genes in rhizosphere strains compared to seed-associated strains, confirming the regulatory function of the aflR gene. Interestingly, maize seeds pre-treated or co-inoculated with certain less aflatoxigenic A. flavus strains exhibited signs of induced resistance, suggesting a possible immunization effect by endophytic aflatoxigenic strains. This finding highlights a potential avenue for biocontrol, warranting further research to elucidate the underlying metabolic pathways and optimize conditions for practical application.